Untreated Giant Macroprolactinoma with Chronic Cerebrospinal Fluid Leakage: An Unusual Complication - Mohamad Nazrulhisham Mad Naser; Nor Azizah Aziz; Noor Khairiah A. Karim (Case Reports in Endocrinology)
Macroprolactinoma has the potential to cause base of skull erosion and often extends into the sphenoid sinus. Rapid shrinkage of this invasive tumor following dopamine agonist therapy has been postulated to cause unplugging of the eroded area, leading to cerebrospinal fluid leakage. To the best of our knowledge, the occurrence of spontaneous cerebrospinal fluid leak in treatment-naive prolactinomas is very rare, the majority of which involve undiagnosed macroprolactinomas. We describe here a lady presented late with giant macroprolactinoma, complicated by cerebrospinal fluid leakage. This case raised the dilemma in the management pertaining to the role of either pharmacotherapy or surgical intervention, or combination of both. As she strictly refused surgery, she was treated with bromocriptine which was later changed to cabergoline. On follow-up, there was cessation of cerebrospinal fluid leak, marked reduction of serum prolactin level, and imaging evidence of tumor shrinkage. The majority of patients with medically induced cerebrospinal fluid leakage will require surgical procedures to overcome this complication; however, there are isolated cases of leakage resolution on continuing dopamine agonist therapy while awaiting surgery. The use of dopamine agonist does not necessarily cause worsening of cerebrospinal fluid leakage and instead may produce spontaneous resolution as in this case.